Introduction to linear algebra - Strang, Gilbert (Wellesley, MA : Wellesley-Cambridge Press, 1998)
This book is about: Solving linear equations; Vector spaces and subspaces; Orthogonality; Determinants; Eigenvalues and Eigenvectors; ...
Keywords: Algebras; Linear of Algebras; Algebra, Linear